Optimizing Osteoarthritis Management: A Systematic Review of Hydrotherapy's Impact on Symptoms and Quality of Life - Tata Mahyuvi (Yayasan Literasi Sains Indonesia, 2025)
Introduction: Osteoarthritis (OA) is a prevalent type of arthritis, particularly among the elderly, and is a leading cause of disability in older adults. Reduced physical activity in OA patients often results in psychological disturbances when visiting healthcare facilities, contributing to a significant burden on healthcare services and diminishing individual quality of life. Objective: This study aims to analyze the literature on the effectiveness of hydrotherapy and land-based physical exercise in addressing osteoarthritis (OA) symptoms. Methods: A systematic literature search was conducted using the PubMed, Semantic Scholar, and OpenAlexa databases up to December 2024. Keywords included